MISO Current-mode Biquad Filter with Independent Control of Pole Frequency and Quality Factor - Jaikla, Winai; Siripongdee, Surapong; Suwanjan, Peerawut (Společnost pro radioelektronické inženýrství, 2012)
This article presents a three-inputs single-output biquadratic filter performing completely standard functions: low-pass, high-pass, band-pass, band-reject and all-pass functions, based on current controlled current conveyor transconductance amplifier (CCCCTA). The quality factor and pole frequency can be electronically/independently tuned via the input bias current. The proposed circuit uses 2 CCCCTAs and 2 grounded capacitors without external any resistors which is very suitable to further develop into an integrated circuit. The filter does not require double input current signal. Each function response can be selected by suitably selecting input signals with digital method. Moreover, the circuit possesses high output impedance which would be an ideal choice for current-mode cascading. The PSPICE simulation results are included to verify the workability of the proposed filter. The given results agree well with the theoretical anticipation.
Keywords: Analog filter; CCCCTA; Current-mode; Multiple input-Single output